2017
DOI: 10.1080/09712119.2017.1284074
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of a combined phytogenic feed additive with an individual essential oil of oregano on intestinal morphology and microflora in broilers

Abstract: The effects of dietary supplementation of oregano essential oil (OEO) and a commercial blend of phytogenic (CBP) on intestinal properties, the number of ileal Escherichia coli and Lactobacillus were investigated in broilers. Two hundred 1-d-old broiler chicks were assigned to 4 dietary treatments that include: (1) Control (without phytogenic), (2) CBP (150 ppm), (3) OEO (300 ppm) and (4) OEO (500 ppm). Each of the 4 diets was fed to 5 replicates of 10 chicks from hatching to 42 d of age. Jejunal and ileal vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
(43 reference statements)
2
23
0
1
Order By: Relevance
“…So, changes in feed and feed additives may affect the morphology of intestine different parts. In this case, Mohiti-Asli and Ghanaatparast-Rashti (2018) compared the effects of a combined phytogenic feed additive (oregano, anise and citrus peel) with oregano essential oil on intestinal morphology in broilers. They reported that broilers fed 300 ppm individual oregano essential oil in their diet had larger villi height, villi surface area, villi height to crypt dept ratio and lower crypt dept in jejunum than those fed either control diet or combined phytogenic feed additive.…”
Section: Resultsmentioning
confidence: 99%
“…So, changes in feed and feed additives may affect the morphology of intestine different parts. In this case, Mohiti-Asli and Ghanaatparast-Rashti (2018) compared the effects of a combined phytogenic feed additive (oregano, anise and citrus peel) with oregano essential oil on intestinal morphology in broilers. They reported that broilers fed 300 ppm individual oregano essential oil in their diet had larger villi height, villi surface area, villi height to crypt dept ratio and lower crypt dept in jejunum than those fed either control diet or combined phytogenic feed additive.…”
Section: Resultsmentioning
confidence: 99%
“…Phytogenic feed additives increase the hydrophobicity of pathogenic bacterial species through modulating their cellular membrane, consequently affecting the surface properties of microbial cells. In this manner, they not only affect the virulence properties of harmful bacteria, but also play a crucial role in bacterial adhesion to mucosal cells, which is dependent on the hydrophobicity of microbial surface cells ( Mohiti-Asli and Ghanaatparast-Rashti, 2018 ). The present study used a blend of different phytogenics, which were recognized to deferentially inhibit pathogenic bacteria and promote beneficial bacterial growth in broiler gut ( Munir, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation of phytobiotics in broilers has considerable positive effects; their supplementation could improve gut health [ 14 , 15 , 16 ], positively modulate the dynamics of gut microbiota [ 17 ], and enhance feed efficiency [ 6 , 18 ], thus, increase growth performance [ 19 , 20 , 21 , 22 , 23 ]. Various studies have established the antibacterial efficacy of phytobiotics against pathogenic bacteria, such as Clostridium and E. coli , in broiler chickens [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%